Do children adopted from British foster care show difficulties in executive functioning and social communication?. (December 2017) - Wretham, Alexandra E; Woolgar, Matt
Early life experiences leave a mark on a child's emotional, social and cognitive development. It is well established that children adopted from psychosocially depriving institutions have difficulties in executive functioning and social communication ability, but this type of research has not been replicated in children adopted from foster care. In this study, 30 primary school aged UK adoptees without a history of institutionalisation completed an assessment of their intellectual, executive functioning and social communication abilities. Compared to children of a similar age in the general population, the adopted group showed elevated emotional and behavioural difficulties on a parental report measure (Strengths and Difficulties Questionnaire, SDQ). They performed statistically poorer on two of three computerised executive functioning tests (CANTAB Intra-Extra Dimensional Shift and Spatial Working Memory) and elevated scores were observed on a parental report measure of executive functioning (Behavior Rating Inventory of Executive Functioning, BRIEF). A strong negative correlation was found between age of adoption and BRIEF scores controlling for ADHD symptoms; no other pre- or post-adoption variables strongly correlated with executive functioning. Although all participants scored below cut-off on an autism screening measure (Social Communication Questionnaire, SCQ), a moderate positive correlation was observed with age of adoption. The identified elevation in emotional, behavioural and executive functioning difficulties is in line with previous research examining children adopted from institutions; however, the observed negative correlation between BRIEF scores and age of adoption is contrary to previous evidence. Limitations and implications for future research are discussed.